The non-compressibility ratio for accurate diagnosis of lower extremity deep vein thrombosis - Caecilia Marliana; A. Gunawan Santoso; Santosa Santosa (Universa Medicina, 2014)
BACKGROUNDAccurate identification of patients with deep vein thrombosis (DVT) is critical,as untreated cases can be fatal. It is well established that the specificity of the clinical signs and symptoms of DVT is low. Therefore, clinicians rely on additional tests to make this diagnosis. There are three modalities for DVT diagnosis; clinical scoring, laboratory investigations, and radiology. The objective of this study was to determine the correlation of plasma D-dimer concentration with the ultrasonographic non-compressibility ratio in patients with DVT in the lower extremities.METHODSThis research was a cross-sectional observational study. The sample comprised 25 subjects over 30 years of age with clinically diagnosed DVT in the lower extremities. In all subjects, D-dimer determination using latex enhanced turbidimetric test was performed, as well as ultrasonographic non-compressibility ratio assessment of the lower extremities. Data were analyzed using Pearson’s correlation at significance level of 0.05.RESULTSMean plasma D-dimer concentration was 2953.00 ± 2054.44 μg/L. The highest mean non-compressibility ratio (59.96 ± 35.98%) was found in the superficial femoral vein and the lowest mean non-compressibility ratio (42.68 ± 33.71%) in the common femoral vein. There was a moderately significant correlation between plasma D-dimer level and non-compressibility ratio in the popliteal vein (r=0.582; p=0.037). In the other veins of the lower extremities, no significant correlation was found.CONCLUSIONThe sonographic non-compressibility ratio is an objective test for quick and accurate diagnosis of lower extremity DVT and for evaluation of DVT severity.